2021
DOI: 10.1021/acs.est.1c00114
|View full text |Cite
|
Sign up to set email alerts
|

Ebullition Controls on CH4 Emissions in an Urban, Eutrophic River: A Potential Time-Scale Bias in Determining the Aquatic CH4 Flux

Abstract: Rivers and streams contribute significant quantities of methane (CH4) to the atmosphere. However, there is a lack of CH4 flux and ebullitive (bubble) emission data from urban rivers, which might lead to large underestimations of global aquatic CH4 emissions. Here, we conducted high-frequency surveys using the boundary layer model (BLM) supplemented with floating chambers (FCs) and bubble traps to investigate the seasonal and diurnal variability in CH4 emissions in a eutrophic urban river and to evaluate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 73 publications
4
23
0
Order By: Relevance
“…To predict CH4 and N2O fluxes from non‐marine waters, linear stepwise regression models with the personality of OSL were used to fit CH4 and N2O fluxes by controlling factors. We found that water DO showed as a dominant factor among all variables to influence CH 4 (diffusive and ebullitive) and N 2 O fluxes from inland waters (Table S3), which was confirmed by previous findings that water DO appears to be strongly related to diffusive and ebullitive CH 4 fluxes in aquatic systems (Beaulieu et al, 2010; Chen et al, 2021). Water DO and DOC together could even explain 60% of the variance in diffusive CH 4 fluxes from inland waters.…”
Section: Discussionsupporting
confidence: 90%
“…To predict CH4 and N2O fluxes from non‐marine waters, linear stepwise regression models with the personality of OSL were used to fit CH4 and N2O fluxes by controlling factors. We found that water DO showed as a dominant factor among all variables to influence CH 4 (diffusive and ebullitive) and N 2 O fluxes from inland waters (Table S3), which was confirmed by previous findings that water DO appears to be strongly related to diffusive and ebullitive CH 4 fluxes in aquatic systems (Beaulieu et al, 2010; Chen et al, 2021). Water DO and DOC together could even explain 60% of the variance in diffusive CH 4 fluxes from inland waters.…”
Section: Discussionsupporting
confidence: 90%
“…Such measurements focus on quantifying the diffusive flux of gases across the air–water surface but hardly capture sporadic bubble transmission (ebullition) by a limited number of gas hoods. Due to the relatively low solubility of CH 4 in water (e.g., 20.3 g/m 3 at 30 °C), CH 4 is often emitted in the form of bubbles that rise directly from the sediments. , Taking CH 4 emissions from inland freshwater ecosystems (e.g., lakes, rivers, and reservoirs) as an example, ebullition contributed up to 99% of the total diffusive and ebullitive flux. , However, there is no information on the contributions of ebullition to the overall CH 4 emission from stabilization ponds. Given stabilization ponds are popular wastewater treatment processes worldwide especially for decentralized and developing communities, more efforts should be carried out to characterize and reduce CH 4 emissions from this type of facility.…”
Section: Resultsmentioning
confidence: 99%
“… 14 , 29 Taking CH 4 emissions from inland freshwater ecosystems (e.g., lakes, rivers, and reservoirs) as an example, ebullition contributed up to 99% of the total diffusive and ebullitive flux. 29 , 51 However, there is no information on the contributions of ebullition to the overall CH 4 emission from stabilization ponds. Given stabilization ponds are popular wastewater treatment processes worldwide especially for decentralized and developing communities, 41 more efforts should be carried out to characterize and reduce CH 4 emissions from this type of facility.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to biogeochemical processes, methane transport within soil and across interfaces is also subject to change with local biological (e.g., vegetation, bioturbation) and physical conditions including hydrology, meteorology, and temperature which also influences methane production and consumption (e.g., Ardón et al., 2018; Bao et al., 2021; Kellner et al., 2006; Tokida et al., 2007). Among different gas transport processes, gas ebullition, unlike plant‐mediated transport which depends on vegetation presence and physiology and growth factors, can occur in aquatic, mudflat and other unvegetated environments (S. Chen et al., 2021; Fechner‐Levy & Hemond, 1996; Gao et al., 2013; Olsen et al., 2019). Meanwhile, compared with diffusion transport, gas ebullition is an important gas transport pathway that could account for the high spatiotemporal variability in field measurements, but it is less understood and quantified in the field due to its episodic behavior (Baird et al., 2004; X. Chen et al., 2017; Tokida et al., 2007; Villa et al., 2021).…”
Section: Introductionmentioning
confidence: 99%